The Music of the Chilean Outburst: the Awakening saw from the Window of the Event (Tempo e Argumento, 2021)
This work is a research exercise about the history of present time in which we show how it is possible to make intelligible facts that are in temporal proximity to the observer. To do so, we take as a case study the Chilean mobilisations of 2019 in Chile and, in particular, a corpus of songs broadcasted on the YouTube channel of Lavitrola.cl under the hashtag #únansealcanto. From an analysis of what musicians’ “sing”, “say” and “do”, we explored how songs could inform and signify an event, as well as how this event could be itself a window to capture the sense of the present, to illuminate its structural dynamics, and to comprehend the aspirations of its main actors pursue.Keywords: event; Chilean social outburst; history of present time; music; digital cultures.